Adaptation of Renewable Energy in SSA: Testing Debt Overhang Hypothesis with the Presences of Political Stability and ICT Development - Qamruzzaman, Md; Manickavasagam, Theivanayaki; Manickavasagam, Ganeshwari (International Journal of Energy Economics and Policy, 2025)
Despite the growing discourse on sustainable energy transitions, limited empirical evidence exists on the macroeconomic and institutional determinants of renewable energy consumption in Sub-Saharan Africa (SSA). This study addresses this critical research gap by investigating the dynamic effects of external debt, ICT development, political stability, urbanization, remittances, and global uncertainty on renewable energy consumption across 25 SSA countries over the period 2000-2021. The research is guided by the following questions: (1) How do external debt and global uncertainty influence renewable energy consumption in SSA? (2) What roles do ICT development, political stability, and urbanization play in shaping the region’s renewable energy trajectory? Using second-generation panel techniques—specifically, the Cross-Sectionally Augmented ARDL (CS-ARDL) model and Dumitrescu–Hurlin panel causality tests—the study uncovers several key findings. Notably, external debt significantly reduces renewable energy consumption in the long run (β = −0.040***), validating the debt-overhang hypothesis. Conversely, ICT development (β = 0.080***) and political stability (β = 0.110***) exhibit strong positive long-run effects, while urbanization also shows long-run benefits (β = 0.081**). In contrast, global uncertainty exerts a significant long-run negative effect (β = −0.064***). These findings are supported by robust causal relationships. The novelty of this study lies in its integrated modeling of fiscal, institutional, technological, and geopolitical variables, providing a holistic understanding of renewable energy dynamics in SSA. It offers clear empirical evidence that coherent debt management, digital infrastructure expansion, and institutional strengthening are vital for achieving energy sustainability in the region.